2021
DOI: 10.1371/journal.pone.0247752
|View full text |Cite
|
Sign up to set email alerts
|

Isoalantolactone inhibits pancreatic cancer proliferation by regulation of PI3K and Wnt signal pathway

Abstract: Background/aims Isoalantolactone (IATL) is one of multiple isomeric sesquiterpene lactones and is isolated from inula helenium. IATL has multiple functions such as antibacterial, antihelminthic and antiproliferative activities. IATL also inhibits pancreatic cancer proliferation and induces apoptosis by increasing ROS production. However, the detailed mechanism of IATL-mediated pancreatic cancer apoptosis remains largely unknown. Methods In current study, pancreatic carcinoma cell lines (PANC-1, AsPC-1, BxPC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…Aberrant activation of different signaling pathways is involved in the pathogenesis of pancreatic cancer. 64 Additionally, inhibition of these proliferative signals showed satisfactory efficacy in preclinical studies of pancreatic cancer. 64 As mentioned previously, KRAS mutation is a major propellant for the initiation and progression of pancreatic cancer.…”
Section: The Effect Of C-myc On Cancer Cells Metabolismmentioning
confidence: 99%
“…Aberrant activation of different signaling pathways is involved in the pathogenesis of pancreatic cancer. 64 Additionally, inhibition of these proliferative signals showed satisfactory efficacy in preclinical studies of pancreatic cancer. 64 As mentioned previously, KRAS mutation is a major propellant for the initiation and progression of pancreatic cancer.…”
Section: The Effect Of C-myc On Cancer Cells Metabolismmentioning
confidence: 99%
“…Apart from IAL [ 202 ], recently particularly ALT has been extensively studied for its cytotoxic and anti-proliferative activity in a variety of human cancer cell lines, including the colon [ 203 ], lung [ 204 ], breast [ 205 ], gastric [ 206 ], pancreatic cancer [ 207 ], leukemia [ 208 ], and glioblastoma multiforme [ 209 ]. The anti-tumor properties of ALT occurred through a wide range of overlapping molecular pathways, interacting with each other [ 180 , 207 ].…”
Section: Essential Oils From Selected Rootsmentioning
confidence: 99%
“…Moreover, a recent study showed that IALT increased phosphorylation of p38 and JNK in breast cancer cells, but not in normal breast cells, and IALT-mediated apoptosis could be abolished by inhibitors of p38 and JNK [ 45 ]. In addition, several previous studies have shown that an increase in ROS production was involved in IALT-induced apoptosis in various types of cancer cells [ 40 , 42 , 43 , 48 , 49 ]. Therefore, we assessed whether the IALT-induced apoptosis of Hep3B cells was related to ROS and investigated the role of ROS in the activation of the MAPK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…IALT has also been extensively reported to exert anti-cancer effects by inducing apoptosis, cell cycle arrest and autophagy in several types of cancer cells, which was confirmed to be selective for cancer cells [ 36 , 37 , 38 , 39 ]. Mechanistically, activation or inhibition of various cellular signaling pathways, including nuclear factor-κB, phosphatidylinositol 3-kinase/Akt, and MAPK, and increased ROS production were found to be involved in the induction of IALT-induced cancer cell apoptosis [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. However, the anti-cancer effects of IALT on HCC cells have not been studied yet.…”
Section: Introductionmentioning
confidence: 99%